High-resolution monochromatic backlit imaging of the Cu Kα characteristic line using a toroidal crystal system for plasma diagnostics - Dong, Ke; Wang, Liwei; Si, Haoxuan; Yi, Shengzhen; Wang, Zhanshan; Shan, Lianqiang; Yu, Minghai; Zhang, Tiankui; Wei, Lai; Chen, Zhongjing; Zhou, Kainan; Zhou, Weimin; et al. (Review of scientific instruments, 2025)
Laser-driven plasma diagnostics commonly rely on high-resolution monochromatic x-ray imaging using α-quartz (211) spherical crystals at an 88.7° Bragg angle for the Cu Kα characteristic line. However, the performance of this imaging approach is constrained by astigmatism-induced resolution limits (<10 μm) and background noise interference. To overcome this, we developed a toroidal crystal system utilizing the fourth-order diffraction of an Si (111) crystal with a Bragg angle of 79.33°, effectively addressing the astigmatism problem associated with traditional spherical crystals and considerably reducing background noise caused by suprathermal electrons. This system demonstrated a spatial resolution of 3-10 μm across a 2 mm field of view (FOV) in offline x-ray experiments. Calibrated tests at the XingGuang III laser facility further confirmed its high signal-to-noise-ratio imaging performance, achieving a spatial resolution of 4-10 μm within a 400 μm FOV. Overall, this study establishes a novel x-ray imaging technique based on a toroidal crystal system, enhancing the quality and reliability of Cu Kα line imaging for laser-driven plasma diagnostics.